2021
DOI: 10.3389/fmicb.2021.732905
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities and Functions in the Rhizosphere of Disease-Resistant and Susceptible Camellia spp.

Abstract: Oil tea (Camellia spp.) is endemic to the hilly regions in the subtropics. Camellia yuhsienensis is resistant to diseases such as anthracnose and root rot, while Camellia oleifera is a high-yield species but susceptible to these diseases. We hypothesize that differences in the rhizosphere microbial communities and functions will elucidate the resistance mechanisms of these species. We used high-throughput sequencing over four seasons to characterize the rhizosphere microbiome of C. oleifera (Rhizo-Sus) and C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…For example, species C. yuhsienensis is resistant to anthracnose, root rot diseases, and root knot nematode, but the high-yielding cultivar "Huashuo" of C.oleifera is susceptible to these diseases (Yang et al, 2004;Tan et al, 2011;Wei et al, 2013;Zhu et al, 2020;Chen et al, 2022b). Further study showed that the abundant and diverse microbial community in C. yuhsienensis rhizosphere may help to protect the host from pathogens (Li et al, 2021a) The plant growth and seed yield of oiltea-camellia are affected by anthracnose, a disease caused by Colletotrichum gloeosporioides. Anthracnose resistance is one of the most important traits for variety development of oiltea-camellia.…”
Section: Disease and Pest Resistancesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, species C. yuhsienensis is resistant to anthracnose, root rot diseases, and root knot nematode, but the high-yielding cultivar "Huashuo" of C.oleifera is susceptible to these diseases (Yang et al, 2004;Tan et al, 2011;Wei et al, 2013;Zhu et al, 2020;Chen et al, 2022b). Further study showed that the abundant and diverse microbial community in C. yuhsienensis rhizosphere may help to protect the host from pathogens (Li et al, 2021a) The plant growth and seed yield of oiltea-camellia are affected by anthracnose, a disease caused by Colletotrichum gloeosporioides. Anthracnose resistance is one of the most important traits for variety development of oiltea-camellia.…”
Section: Disease and Pest Resistancesmentioning
confidence: 99%
“…For example, species C. yuhsienensis is resistant to anthracnose, root rot diseases, and root knot nematode, but the high-yielding cultivar “Huashuo” of C.oleifera is susceptible to these diseases ( Yang et al., 2004 ; Tan et al., 2011 ; Wei et al., 2013 ; Zhu et al., 2020 ; Chen et al., 2022b ). Further study showed that the abundant and diverse microbial community in C. yuhsienensis rhizosphere may help to protect the host from pathogens ( Li et al., 2021a )…”
Section: Genes For Abiotic Stress Tolerance and Biotic Stress Resistancementioning
confidence: 99%
“…Plant growth in variable environment is threatened by various biotic stresses such as pathogen, and gradually domesticate the corresponding resistance mechanisms (Bakker et al ., 2018 ; Chen et al ., 2020 ; Li et al ., 2021 ; Liu et al ., 2020 , 2021 ; Song et al ., 2021 ). When plants are invaded by pathogens, disease resistance genes will be activated, which in turn trigger plant‐specific molecular immune recognition systems (Teixeira et al ., 2019 ).…”
Section: Plant Functional Genes Regulate Rhizosphere Microorganismsmentioning
confidence: 99%
“…The rhizosphere is a microhabitat in a narrow zone of soil surrounding plant roots with a high abundance of microorganisms (Kuzyakov & Razavi, 2019; Vetterlein et al, 2020). Microorganisms in the rhizosphere are directly influenced by host plants and are indirectly influenced by some environmental conditions (Li et al, 2021; Zhang et al, 2020). In the rhizosphere, plants release root exudates to promote bacterial community development (Caracciolo & Terenzi, 2021).…”
Section: Introductionmentioning
confidence: 99%